1998
DOI: 10.1001/archsurg.133.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Completion Total Thyroidectomy in Children With Thyroid Cancer Secondary to the Chernobyl Accident

Abstract: Objective: To evaluate the usefulness of submitting children with thyroid cancer secondary to nuclear accidents to a completion total thyroidectomy. Design: A case series consisting of patients living and operated on in Belarus whose parents had asked for a clinical evaluation in a western European center. Setting: A tertiary care referral center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 15 publications
0
49
0
2
Order By: Relevance
“…This also applies to children and young adults, because 60-80% have regional lymph node involvement and 10-20% have distant metastases (Mazzaferri 1991, Hay et al 1998, Miccoli et al 1998, Newman et al 1998www.endocrinology.org 233 berger 1998, La Quaglia et al 2000). Of 50 children aged 15 or younger in our study, 28% developed distant metastases, usually to lung.…”
Section: Consensus Recommendationsmentioning
confidence: 51%
See 2 more Smart Citations
“…This also applies to children and young adults, because 60-80% have regional lymph node involvement and 10-20% have distant metastases (Mazzaferri 1991, Hay et al 1998, Miccoli et al 1998, Newman et al 1998www.endocrinology.org 233 berger 1998, La Quaglia et al 2000). Of 50 children aged 15 or younger in our study, 28% developed distant metastases, usually to lung.…”
Section: Consensus Recommendationsmentioning
confidence: 51%
“…Cancer is found in the contralateral lobe in about 50% of cases (Pasieka et al 1992, Mazzaferri 2000. Lung and lymph node metastases in more than 60% of a group of irradiated children from Chernobyl could only be identified after completion thyroidectomy had been done (Miccoli et al 1998). In another important study, multivariate analysis found that patients who underwent completion thyroidectomy within 6 months of their initial operation developed significantly fewer lymph node and hematogenous recurrences and survived significantly longer than those in whom the second operation was delayed for longer than 6 months (Scheumann et al 1996).…”
Section: Completion Thyroidectomymentioning
confidence: 99%
See 1 more Smart Citation
“…A varredura com radioiodo tem sua sensibilidade para metástases reduzida se a cirurgia inicial for a lobectomia, pelo seqüestro do traçador pelos remanescentes tireoideanos (26). Miccoli e cols.…”
Section: Discussionunclassified
“…However, serum calcium tests, probably much more frequent in the West, potentially conductive to detection and treatment of hyperparathyroidism [35], could have contributed to a lower prevalence of this condition among the controls in [33]. On the other hand, the risk of postsurgical hyperparathyroidism (6 % of operated pediatric TC cases [25]; 10,5 % of those undergoing completion total thyroidectomy [36]), recurrent nerve palsy etc. [20,37], are among reasons why false-positive diagnosis should be precluded.…”
Section: Introductionmentioning
confidence: 99%